Scaling of correlation length in lamellae forming PS-b-PMMA thin films upon high temperature rapid thermal treatments1. Issue 33 (7th September 2015) - Ceresoli, M.; Volpe, F. G.; Seguini, G.; Antonioli, D.; Gianotti, V.; Sparnacci, K.; Laus, M.; Perego, M.
<x xml:space="preserve">Abstract</x> Highly ordered lamellar grains were produced by thermal treatment of the samples in a rapid thermal processing machine. The processing parameters that maximize the lateral order avoiding any degradation of the macromolecules were identified.